Penerapan CHSE Dalam Pelayanan Bellman Di Jumana Bali Ungasan Resort - I Made Jaka Yunantha; Ni ketut iswarini (Journal of Hospitality Accommodation Management (JHAM), 2022)
The implementation of CHSE in the bellman service at Jumana Bali Ungasan Resort, during the pandemic, needs to be investigated, because there are guest complaints regarding the bellman service that has not been maximized, resulting in complaints. This complaint will have an impact on the image of the hotel. This study aims to contribute ideas and descriptions for decision makers in improving bellman's services for the implementation of CHSE at Jumana Bali Ungasan. Data collection techniques are observation, interviews and documentation. The analytical technique used is descriptive qualitative, namely by describing the application of CHSE in Bellman services with reference to standard operating procedures for bellman services during a pandemic. sanitizer and keeping a distance and 32% have not maximally applied standards such as using hand gloves which are sometimes too late, filling in tissues that are often late has not been intensive in spraying disinfectants to buggy cars. Supervision from bellman's superiors will greatly help to improve the implementation of CHSE.